(untitled) (Journal of Universal Science Research, 2023)
This is it article English and Uzbek of the concept of " Honesty " in their languages semantic to the analysis is dedicated. Also this " Honesty " concept in the article English and Uzbek in linguistic culture similarity and different aspects are also open is given Honesty of the lexeme main, important features moral narrow group interests, ideological or practical from thoughts, corporate superior to put honesty lexeme of norms objective content reflection bringer universal call it nature need